The Portrait of Market Leader in Flower Market Vendors at Pasar Rawa Belong - R.A. Aryanti W. Puspokusumo (Bina Nusantara University, 2013)
A good prospect in flowers’ business has made many newcomers from different cities interested in trying the opportunity to become a succesful florist. Since Pasar Rawa Belong has grown up and become more well-known as the marketing and promotion center for flowers, it creates a conducive and atmospheric place to start the business. Many florists in Pasar Rawa Belong have made big profits from the businesses. It can be said that they all are successful florists. However, there will be barely a single florist who is considerately leading forward in the competitive environment. An observation through population of all florists in Pasar Rawa Belong and samples of 50 florists was done in order to find the forthcoming market leader. The method used in observing florists in Pasar Rawa Belong was survey and interview. Next, the results were summarized and analyzed based on certain theoremes from textbooks, articles, and online documents. The theorems are mostly related to management aspects of a competitive and conducive environment while operating a business. According to the data, Yurie Florist, Kusumawardani, and Anadisha come out as the market leaders in 2011 since they have the highest sales per month or beyond 100 million. Meanwhile, no more than 16 percent of florists in Pasar Rawa Belong are able to gain profit of more than 100 million rupiahs per month. Yurie Florist, Kusumawardani, and Anadisha have wide-scale of distribution channels and sells imported flowers which support their high sales. The sales become indicator to determine market share of the shops. The market share itself is decisive indicator to determine the market leader